Review of trade policy instruments and administrative practices governing the operation of the CARICOM CET and rules of Origin : final report (Trevor Hamilton and Associates KingstonJM)
Describes and analyzes the administrative practices and procedures to determine their compatibilities with the objectives of the CET and the Rules of Origin. Sets out the critical challenges which must be addressed in order to ensure that the CET and Rules of Orgin enhances economic equity, promotes economic competitiveness, modernizes the traditional economic sectors, removes unfair trading practices, and reponds to new and emerging structural developments in the community's varied national economies. Recommends the strategic interventions that CARICOM should implement to address these issues.
Limited circulation